Quality of Life (QOL) assessment among advance cancer patient undergoing palliative treatment in Malaysia: A social work perspective - Wanda Kiyah George Albert; Adi Fahrudin (Horizon Research Publishing, 2017)
Palliative treatment is the best treatment for advanced cancer patients improve their quality of life (QOL). There is a lack of local data on the patients' QOL among cancer patient receiving palliative treatment in a university medical center in Malaysia. This study aims to describe QOL among patients with advance cancer disease receiving palliative treatment in a teaching hospital in Kuala Lumpur. This was a cross-sectional study that has been done with 120 of cancer patients that receiving palliative treatment using convenience sampling. The SF-36 questionnaire has been used to measures Quality of Life (QOL) across eight domains based on physically and emotionally component summary. Results showed that the highest score of QOL were observed in the Mental Component Summary (44.93± 6.84) compared with Physical Component Summary at (42.24± 7.91). More studies are needed to investigate patients who score poorly on physical and mental component aspects to understand their needs in order to achieve better cancer care especially in social work perspective.